Design System analysis of linear regression and correlation of Harddisk prices and the dollar prices Using Visual Basic 6.0 - author author (Jurnal Sistem Informasi, 2006)
In scientific writing the author only discusses this regression analysis and general linear correlation which describes the relationship of two variables as the price of hard disk and Y variables as the dollar price of the variable X. The purpose of this scientific writing is to get the results of regression analysis equations and simple linear correlation to make a prediction or a more accurate estimate to assist the suppliers or the public to know the price level hard drive on the market to determine the future activities more profitable.